Awareness and Knowledge Regarding Infant and Young Child Feeding (IYCF) Practice among House Officers Versus General Practitioner - Yasmeen Memon, Shazia Memon, Muhammad Nadeem Chohan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the awareness and knowledge regarding IYCF practice among House Officers versus general practitioner Study Design: Cross sectional comparative study Place and duration of study: Pediatric Department LUMHS from January 2018 to June 2018 Methodology: A total of 200 doctors were selected with non-probability purposive sampling technique and divided equally in Group A (House Officers and Group B (General Practitioner) for our convenience. A total of 100 fresh medical graduates (House Officers) and 100 general practitioner of at least 3 years’ experience were included in the study. A structured questionnaire was use to collect the information regarding awareness of IYCF. Two groups were compared by using Chi square test and p value <0.05 was considered statistically significant. Results: A total of 200 participants were divided in two groups, Group A consist of 100 house officers and Group B 100 general practitioner. Thirty questions were asked from each participants and response rate was 100%. For one question both groups answered 100%, for 27 questions house officers gave correct answers as compared to general practitioner, while for 2 questions general practitioner answers correctly then the house officers. Conclusion: Fresh Doctors (House officers had better knowledge regarding the IYCF practice as compared to General Practitioner. General Practitioner should be trained for IYCF and it should be a part of curriculum of final years MBBS students.